The accumulation of disadvantage: criminaljustice contact, credit, and debt in the transitionto adulthood - DeMarco, Laura M. (Criminology, 2021)
Social exclusion of those with criminal justice experience increasingly includes a financial component, but the structure of disadvantage in credit and debt remains unclear. We develop a model of financial disadvantage in debt holding during the transition to adulthood among justice-involved groups. We study cumulative criminal justice contact and debt holding by age 30 using the National Longitudinal Survey of Youth 1997 (NLSY97). The NLSY97 cohort transitioned to adulthood during an era of historically high criminal justice contact, with many experiencing arrests, convictions, and incarceration. We develop a distinct measurement approach to cumulative criminal justice contact by age 30 that captures variation between young adults in the severity of justice encounters in the early life course. We conceptualize financial disadvantage as a lower likelihood of holding debt that facilitates property and attainment investments and a higher likelihood of holding higher cost debts used for consumption or emergencies. We find that those with the most punitive criminal justice contact evidence the most disadvantageous form of debt holding, potentially exacerbating social exclusion. We consider the implications of the accumulation of financial disadvantage for our understanding of criminal justice contact as a life-course process.